AB0565 Routine Investigations for Circulating Igg4 and/or Igg4+ Salivary Gland Histopathology Fail to Reveal Undiagnosed Cases of Igg4 Related Disease in Sicca Patients not Fulfilling the Diagnosis of Sjogren's Syndrome. (9th June 2015) - Astorri, E.; Croia, C.; Picarelli, G.; Sutcliffe, N.; Tappuni, A.; Bombardieri, M.; Priori, R.
Abstract : Background: Immunoglobulin G4 (IgG4)-related disease (IgG4-RD) is an immune-mediated condition characterized by dense IgG4+ plasmacytic infiltration of diverse organs, fibrosis, tumefactive lesions and eosinophilia. Salivary and lacrimal glands are frequent targets that can present with enlargement and severe hypofunction. The diagnosis of IgG4-RD is challenging because of its serological and histopathological overlaps with other diseases, in particular, a differential diagnosis with Sjogren's syndrome (SS) can sometimes be achieved only on the basis of a labial salivary gland biopsy. Objectives: In this study we evaluated whether some of the patients with sicca symptoms not fulfilling SS classification criteria, were in fact affected by IgG4-RD. Methods: A total of 81 Sicca and 50 SS patients were retrospectively evaluated for IgG4-RD-associated signs and symptoms. Additionally, IgG4 and total-IgG staining was performed on lip gland biopsies from all patients while IgG4 serum levels were evaluated on the Italian cohort. Results: Only 2 of the Sicca patients had positive IgG4 staining but did not fulfil the diagnostic criteria. The serum analysis found 3 sicca patients with raised IgG4 (≥1.35 g/L) but none had a concomitant positive histology nor IgG4-RD related symptoms. Conclusions: In our cohort of patients with sicca symptoms not fulfilling SS criteria no case could be accounted as an undiagnosed IgG4-RD based upon IgG4 staining on labial salivary gland biopsies. This study also suggests that in the absence of a clear clinical suspicious of an IgG4-RD, a routine IgG4 staining on labial salivary gland biopsies is not of clinical utility. References: Yamamoto M, Harada S, Ohara M, Suzuki C, Naishiro Y, Yamamoto H, et al. Clinical and pathological differences between Mikulicz's disease and Sjogren's syndrome. Rheumatology (Oxford). 2005 Feb;44(2):227-34. PubMed PMID: 15509627. Umehara H, Okazaki K, Masaki Y, Kawano M, Yamamoto M, Saeki T, et al. Comprehensive diagnostic criteria for IgG4-related disease (IgG4-RD), 2011. Mod Rheumatol. 2012 Feb;22(1):21-30. PubMed PMID: 22218969. Disclosure of Interest: None declared